2002
DOI: 10.1080/00288233.2002.9513518
|View full text |Cite
|
Sign up to set email alerts
|

Agronomical and physiological responses of white clover(Trifolium repens)and perennial ryegrass(Lolium perenne)to nitrogen fertiliser applied in autumn and winter

Abstract: Mixed pastures of white clover and ryegrass are profitable and widely used. However, loss of clover is common with time due to N fertiliser applications in late winter. The factors that cause this loss have yet to be determined. This work investigated reasons for the competitive disadvantage suffered by white clover relative to ryegrass in autumn and winter. White clover (Trifolium repens cv. 'Grasslands Huia') and ryegrass (Lolium perenne cv. 'Grasslands Nui') were sown in March in Canterbury, New Zealand, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In other systems less limited by nitrogen, grasses can successfully suppress the legumes (Haynes ; Elgersma, Schlepers & Nassiri ; Castle et al . ). However, this happens typically in fairly nutrient‐rich systems where nutrients are provided by some external source (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In other systems less limited by nitrogen, grasses can successfully suppress the legumes (Haynes ; Elgersma, Schlepers & Nassiri ; Castle et al . ). However, this happens typically in fairly nutrient‐rich systems where nutrients are provided by some external source (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…However, this does not need to be a universal finding: our system is only one example of a semi-natural grassland (for which fortunately we have long-term data). In other systems less limited by nitrogen, grasses can successfully suppress the legumes (Haynes 1980;Elgersma, Schlepers & Nassiri 2000;Castle et al 2002). However, this happens typically in fairly nutrient-rich systems where nutrients are provided by some external source (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and Morrison (1997) in a study of spring fertilizer N on ryegrass-white clover swards grazed by beef cattle reported that there was no effect of spring fertilizer N on white clover proportion in the sward over the season as a whole and the use of extra N did not have a significant effect on white clover plants leaf area. Further, white clover dry weight and total shoot and root proportion did not respond to an application of N (Castle et al, 2002). Further evidence to support these claims on a general negative correlation of mineral N use on clover swards has been documented.…”
Section: Growth and Persistencementioning
confidence: 91%
“…Thus, there is a great range of plant responses to NH 4 + nutrition; there are some species that are tolerant to high NH 4 + doses, such as rice (Wang et al, 1993), and some very sensitive species, which are almost unable to live under NH 4 + nutrition, such as tomato or barley (Magalhaes and Huber, 1989;Britto et al, 2001). Reports about the nitrogen form effect in grassland species are rare and, in general, are focused on high and low availability of nitrate (Castle et al, 2002;MacDuff et al, 2002;Collins et al, 2003). Tolerance to NH 4 + -based nutrition could be expected in these species because intensive grazing process leads to urea deposition in grasslands and, consequently, maintained NH 4 + availability in the soil.…”
Section: Introductionmentioning
confidence: 97%